Andreev reflection of massive pseudospin-1 fermions. (1st April 2022) - Zeng, W; Shen, R
Abstract: We theoretically investigate the Andreev reflection of the massive pseudospin-1 Dirac fermions including the + U -type, the − U -type, and the S z -type mass terms, corresponding to the flat band locating at the top, the bottom, and the center of the band gap, respectively. For the ± U -type fermions, it is found that the Andreev reflection probability at the oblique incidence can be even larger than that at the normal incidence. For the retro-reflection, such an oblique enhancement occurs in the n -doped + U -type ( p -doped − U -type) massive fermion systems. While for the specular reflection, the enhancement occurs in the n -doped − U -type ( p -doped + U -type) systems. For the S z -type massive fermions, an ideal Andreev reflection with all-angle unit efficiency is predicted in an undoped junction with the incident energy equal to the superconducting gap.